2017
DOI: 10.1002/cphc.201700299
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Design of DNP Polarizing Agents: Can Current Dinitroxides Be Improved?

Abstract: Numerical calculations of enhancement factors offered by dynamic nuclear polarization in solids under magic angle spinning (DNP-MAS) were performed to determine the optimal EPR parameters for a dinitroxide polarizing agent. We found that the DNP performance of a biradical is more tolerant to the relative orientation of the two nitroxide moieties than previously thought. Generally, any condition in which the g tensor components of both radicals are perpendicular to one another is expected to have near-optimal D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…Dipolar interactions between the 2 nitroxides can be designed to match the nuclear Zeeman frequency. Studies of many dinitroxides demonstrate that the largest DNP enhancements are achieved with rigid linkages that orient the g yy tensors orthogonal to one another . Spiro linkages assisted in creating orthogonal arrangements of the g tensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dipolar interactions between the 2 nitroxides can be designed to match the nuclear Zeeman frequency. Studies of many dinitroxides demonstrate that the largest DNP enhancements are achieved with rigid linkages that orient the g yy tensors orthogonal to one another . Spiro linkages assisted in creating orthogonal arrangements of the g tensors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of many dinitroxides demonstrate that the largest DNP enhancements are achieved with rigid linkages that orient the g yy tensors orthogonal to one another. 8,[11][12][13][14][15][16][17][18] Spiro linkages assisted in creating orthogonal arrangements of the g tensors. DNP enhancement is increased by increasing the saturation factor that depends on the T 1 T 2 product.…”
mentioning
confidence: 99%
“…13,[20][21][22][23] A recent in silico study of the design of dinitroxide polarization agents has, however, concluded that there is little room remaining for improvement within this family of polarizing agents. 24 Nevertheless, other developments, such as the discovery of the Overhauser effect in insulating solids [25][26][27] and the synthesis of trityl-nitroxide biradicals, 28 promise to greatly improve DNP at ultra-high magnetic fields for which they are already outperforming dinitroxides. 27,28 A highly efficient in silico quantum-mechanical treatment would greatly help in better understanding the mechanisms of MAS DNP and guide further advancements of the technique, but carrying it out over the relevant time scales presents a large computational challenge.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this, all quantum mechanical MAS DNP simulations have, to date, been performed on small spin systems (most consisting only of a single nuclear spin with two electrons). 24,[29][30][31][32][33][34] Second, DNP is a very slow process, requiring several seconds to reach equilibrium, which nonetheless depends on a series of very rapid (<1 ns) processes due to the large sizes of the radical's interactions. The spin dynamics must then be calculated using gargantuan matrices for several seconds in nanosecond increments.…”
Section: Introductionmentioning
confidence: 99%
“…This enables for the first time the investigation of the polarization dynamics of hundreds of interacting nuclei on an individual spin level. Our study paves the way towards a systematic analysis, utilization and optimization of realistic many-body CE DNP and may serve as a guidance for the design of optimal DNP regimes and tailor-made polarising agents (biradicals) [22][23][24][25][26][27][28]. Furthermore, we expect our insights to be applicable to the non-equilibrium dynamics of nitrogen-vacancies in diamond [29,30], which is becoming a popular platform for the implementation of quantum sensing and diagnostics.…”
mentioning
confidence: 99%